2014
DOI: 10.2340/00015555-1817
|View full text |Cite
|
Sign up to set email alerts
|

Onychophagia is Associated with Impairment of Quality of Life

Abstract: Onychophagia is defined as a chronic nail biting behaviour affecting about 20-30% of the general population. However, nail biting seems to be an ignored problem in a daily clinical practice. We have analysed the influence of onychophagia on quality of life (QoL) and stigmatisation level among 339 medical students with and without nail biting. Those with onychophagia demonstrated significantly higher QoL impairment compared to the controls (p < 0.001). Subjects who had been unable to stop nail biting behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
2
21
0
5
Order By: Relevance
“…During clenching, masseter and temporalis are similarly recruited, but during incisal biting masseter muscles are dominant over the temporalis muscles . Incisal biting (for example, during nail biting) seems to be related to anxious and depressed personality disposition . This, in turn, might have caused a difference in pain outcomes only for the masseter muscle.…”
Section: Discussionmentioning
confidence: 99%
“…During clenching, masseter and temporalis are similarly recruited, but during incisal biting masseter muscles are dominant over the temporalis muscles . Incisal biting (for example, during nail biting) seems to be related to anxious and depressed personality disposition . This, in turn, might have caused a difference in pain outcomes only for the masseter muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is another possible result of nail‐biting, which leads not only to local infections (e.g., chronic paronychia, subungual infection, onychomycosis, severe damage to the nail bed causing onycholysis), but also to systemic infections. It is reported that a significantly higher prevalence of Escherichia coli and Enterobacteriaceae is found in nail‐biters compared to other people (Baydaş, Uslu, Yavuz, Ceylan, & Dağsuyu, ; Pacan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the nail‐biting habit starts at the age of 3 or 4, worsens at the age of 5 or 6 and in adolescence, and diminishes after the age of 18 (Ghanizadeh, ; Pacan, Reich, Grzesiak, & Szepıetowskı, ; Tanaka et al., ). International literature reports that the prevalence of nail‐biting ranges between 25.5% and 36% among children (Ghanizadeh, ; Pacan et al., ) while it ranges between 12.9% and 68.9% in the national literature (Ergun, Toprak, & Sisman, ; Sisman, Tok, & Ergun, ; Yıldırım, Bayram, Patır, Yalçın, & Seymen, ). However, nail‐biting seems to be ignored in daily clinical practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wearable device, detecting hand-tomouth habits in real-time, would mitigate these impediments, advancing therapeutic interventions and personal health monitoring. With aetiologies including anxiety, loneliness, frustration, and more, such a device could even serve as a diagnostic tool to reflect on quality of life impairments (Pacan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%